The Correlation Between Students’ Vocabulary Mastery and the Ability to Translate English Descriptive Text into Indonesian - Adimas Jaka Pratama; Sayit Abdul Karim; Gordan Matas; Suryo Sudiro (Journal of Languages and Language Teaching, 2024)
Vocabulary and translation are two aspects that have a close relationship in learning English as  to be able to translate a text student should have adequate vocabulary mastery. The presented study aims to figure out the correlation between students’ vocabulary mastery and their translation ability, and to explore their problems in translating English descriptive text into Indonesian. This study applied quantitative research by using the correlational method, and the respondents were 32 students of grade X C at SMAN 1 Purwanegara, Central Java. Furthermore, in order to gather the data, researchers used tests and semi-structured interviews. The data were analysed using Pearson-Product Moment correlation using SPSS 26.0. The findings revealed that the mean score of students’ vocabulary mastery was 66.72, and the mean score of translation ability was 63.72. Meanwhile, the correlation value (r) between the vocabulary mastery and English-Indonesian translation ability score is 0.786. Thus, based on the interpretation score of correlation proposed by Sugiyono (2018), the correlation between vocabulary mastery and the ability to translate the descriptive text was in the high category (0.786), Furthermore, the result of hypothesis testing revealed that the comparison of the “rcount” and the “rtable” shows that rcount as much as 0,786 is clearly higher than “rtable” value which is 5% or 0,338 and 1% or 0,435. Therefore, there is a high correlation between students' vocabulary mastery and their ability to translate descriptive text into Indonesian.